KINETIKA REAKSI PADA PIROLISIS AMPAS TEBU (BAGASSE) - , Emi Erawati, Prof. Ir. Wahyudi Budi Sediawan, S.U., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bagasse is a waste of sugar mills that can be utilized for a variety of chemicals. The purposes of this study are to determine the percentage of the compounds and physical properties of bio-oil, gas composition and calorific value of bio-char bagasse pyrolysis results, to determine the effect of variations of particle size and heating rate on the yields of bio-oil, gas, and char, and to determine models suitable to the bagasse pyrolysis of variation of particle size and heating rate. Pyrolysis has been carried out in a reactor made of steel pipe type 5737 with dimension: diameter 7.62 cm and length 37 cm in length. The reactor was inserted into the furnace with a diameter of 15.24 cm and a length of 40 cm. One hundred and fifty grams of bagasse (Saccarum Oficinarum L) has been inserted into the reactor without the presence of oxygen at atmospheric pressure. Pyrolysis has been carried out at the particle size of 20, 25, 30, 35, and 40 mesh and heating rate of 100, 105, 115, and 120 volt. Produced bio-oil has the following properties: brown colour, pH of 2.96 to 3.03, viscosity of 1.3306 to 1.5101 cp, and density of 1.03 to 1.5 g/mL. The largest content of the compound is acetic acid (59,72%). The composition of the resulting gas consists of CO, CO2, and hydrocarbons. Resulted char has average calorific value of 5,495.97 cal/g and that contains final cellulose of 0.36 (wt%). The assumsion in the research are batch reactor, steady state, lumped model, constant physical properties, and nonisothermal. Modification of Koufopanos mechanism which describes four reaction stages, namely the reaction of virgin material to produce intermediate and the reaction of intermediate to produce gases, bio-oil, and char, was the most appropriate reaction model to predict mass of gas, bio-oil, and char product. The study gives the value of activation energi of E1 8,750.45J/mol, E2 2,350.7 J/mol, E3 11,080.97 J/mol, E4 6,625.49 J/mol while pre-exponential factor of A1 9.20x10-3 second, A2 2.13x10-2 second, A3 1.67 second, and A4 2.31 second for various size particle and heating rate.